Microscopy-Based Studies - Brígido, Clarisse (2022)
Successful colonization of plants by endophytes is the basic requirement for plant-microbe interactions. Thus, the study of plant colonization routes and niches has always been a central aspect in research on plant-microbe interaction. Endophytic microorganisms can be detected by several methods based on microscopy, thus allowing to investigate their behavior, their niches, and how they colonize their hosts. Different techniques can be applied, depending on the study objectives, to single strains or to more complex plant-microbe systems involving full or synthetic microbiomes. Furthermore, the use of microscopy-based tools allows us to track endophytes in plant tissues and to determine how they interact with each other and with their host plants, as well as how they are associated with various plant organs under different plant growth and environmental conditions either from natural or artificial environments. This chapter describes the step-by-step protocol of distinct microscopy-based methods that may be used to visualize and track endophytic microorganisms within plant tissues.